THE IMPORTANCE OF INNOVATIVE EXERCISES IN IMPROVING THE VOCABULARY COMPETENCE OF FOOD TECHNOLOGY STUDENTS - Jabborova Dilfuza G‘ayratovna (Western European Studies, 2024)
This article investigates the effectiveness of innovative teaching methods in enhancing the vocabulary competence of food technology students. By incorporating interactive exercises, project-based learning, and digital tools, this study aims to demonstrate the positive impact of these approaches on students' vocabulary acquisition and retention. The research methodology involved a comparative analysis of two groups: an experimental group exposed to innovative methods and a control group following traditional teaching methods. The results revealed that the experimental group exhibited significant improvements in vocabulary knowledge, comprehension, and usage. The study concludes that innovative exercises can significantly enhance the vocabulary competence of food technology students, leading to improved academic performance and professional readiness
Keywords: vocabulary competence; innovative teaching methods; digital tools